2021
DOI: 10.1109/ojies.2021.3050214
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Reduced Switch Count Multilevel Inverters

Abstract: An efficient and cost-effective power converter is a pre-requisite for the modern power applications. With the evolvement of matured medium power self-commutated switching devices, multilevel inverters (MLIs) are emerged as a promising solution for high-power medium-voltage applications. Though, MLIs are performing a promising role in industrial applications, their high device count, size, cost and control complexity have restricted their market penetration. To address the disadvantages of MLIs, researchers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 179 publications
(301 reference statements)
0
54
0
Order By: Relevance
“…There are three basic multilevel topologies [9,[12][13][14][16][17][18]: NPC, flying capacitor, and cascaded H-bridge. Starting from the original version of these basic topologies, a number of different multilevel topologies have been developed, such as the modular multilevel converter [19], the stacked multicell converter [20], the multilevel active-clamped converter [21], and reduced switch count converters [22].…”
Section: Introductionmentioning
confidence: 99%
“…There are three basic multilevel topologies [9,[12][13][14][16][17][18]: NPC, flying capacitor, and cascaded H-bridge. Starting from the original version of these basic topologies, a number of different multilevel topologies have been developed, such as the modular multilevel converter [19], the stacked multicell converter [20], the multilevel active-clamped converter [21], and reduced switch count converters [22].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the performance and reliability of the inverters used are important parameters that can intensely affect the energy production and economic profitability of PV systems. Thus, PV inverters are moving in the direction of Multilevel Inverter (MLI) topologies to further improve the power quality, reduce the weight of passive filter components, and eliminate bulky transformers [4]- [10]. Among the widely used MLIs, the Flying Capacitors Inverter (FCI) is considered as an interesting topology due to the following advantages: 1) A single DC-source MLI where the number of output voltage levels can be expanded by connecting more cells in series; 2) Provides an extended range of control actions and improves filter bandwidth taking advantage from the switching state redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, an extensive review of recently reported reduced switch count MLIs has been presented 22. This have evolved from a theoretical concept to real applications due to several remarkable features such as possibility of connecting directly to medium voltage, reduction in DC sources and semiconductor devices and their associated gate driver circuits, increased efficiency, less cost, and small size.…”
Section: Introductionmentioning
confidence: 99%